Pediatrics Ewing's Sarcoma of the Sinonasal Tract: A Case Report and Literature Review - Ahmed Aldandan; Ali ‎ Almomen; Abdulrahman Alkhatib; Ghaleb Alazzeh (Hindawi Limited, 2019)
Ewing's sarcoma (ES) is a highly malignant, small, round cell tumor that originates from the primitive neuroectodermal cells. Primary ES commonly occurs in early childhood or adolescence. It may present with skeletal and extraskeletal forms. The extraskeletal form is rarely encountered in the head and neck region and is extremely rare in the sinonasal tract. This is a case report of sinonasal ES in a 13-year-old female patient who presented with a 7-month history of right nasal obstruction, anosmia, intermittent epistaxis, snoring, and hearing loss. Clinical examination revealed a right nasal mass pushing the septum to the left side and extending to the nasopharynx. Endoscopic biopsy and histopathological analysis showed a small blue cell tumor suggestive of ES. The patient was treated with surgery, radiotherapy, and chemotherapy. After a follow-up of 5 years, the patient remains recurrence-free with excellent functional status and quality of life.